Prevalence of hyperuricemia in preeclampsia: A systematic review and meta-analysis of studies from low - and middle - income countries - Fatima Abdirizak Muse; Theoneste Hakizimana; Sowda Abdikarim; Deqa Abdulsalam; Fardowso Dahir Warsame; Fatima Abdallah Noor; Luswata Herbert; Hamdi Jama; Akankwasa Prosper; Jackson Kakooza; Catherine Lewis; Fathi Ali Araye; et al. (PLoS ONE, 2026)
Background Hyperuricemia is a recognized biochemical finding in preeclampsia (PE), but the reported frequency varies across low- and middle-income countries (LMICs). A pooled estimate from LMIC settings may help clarify the extent of this finding in hospital-based populations. Objective To estimate the pooled prevalence of hyperuricemia among women with preeclampsia in hospital-based studies from LMICs. Methods A systematic review and meta-analysis was conducted according to PRISMA guidelines and registered in PROSPERO (CRD420251107624). PubMed, Scopus, Web of Science, and Lens.org were searched for observational studies published from 2010 to 2025 reporting hyperuricemia among women with preeclampsia in LMIC hospital settings. Prevalence estimates were pooled using a random-effects model with logit transformation. Heterogeneity was assessed using Cochran’s Q, Tau², and I². Sensitivity analyses included subgrouping by hyperuricemia threshold and leave-one-out analysis. Results Eleven studies involving 1,099 women with preeclampsia from seven LMICs were included. The pooled prevalence of hyperuricemia was 53.47% (95% CI: 45.17% to 61.58%), with low-to-moderate heterogeneity (I² = 27.47%, p = 0.204). Included studies used different diagnostic thresholds for hyperuricemia, ranging from 5.0 to 7.0 mg/dL. All studies were hospital-based, and reporting of gestational age at the time of uric acid measurement was inconsistent. Conclusions Hyperuricemia was common among women with preeclampsia in hospital-based LMIC studies. These findings describe prevalence only and should not be interpreted as evidence of diagnostic accuracy, prognostic performance, or clinical utility. Future studies should standardize diagnostic thresholds and report gestational timing of uric acid measurement more consistently.